A Note on Contemporary Hui Mosque: Islamic Education in China and its Difficulties - Zhenyu, Sun (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A Note on Contemporary Hui Mosque: Islamic Education in China and its Difficulties